Mesenteric arteritis. Issue 8 (August 1990) - Mosley, J G; Desai, A; Gupta, I
Abstract : Four patients are presented with small bowel infarction secondary to a vascular arteritis. In three patients there was a history of rheumatoid arthritis. In each patient infarcted bowel was resected and a primary anastomosis performed. In one patient the anastomosis broke down and she subsequently died. One patient died from a disseminated rectal tumour three years later. The remaining patients remain well. If operated on early, intestinal infarction due to arteritis has a good prognosis.